Trees as Nature-Based Solutions: A Global South Perspective - Ratnam, Jayashree (2020)
In the search for ways to address sustainability challenges, there is growing interest in nature-based solutions. Among these are calls to plant a trillion trees globally, which have been met with mixed responses. In this Voices, we ask researchers about the potential role of trees in mitigating and adapting to global change, as well as doing so in a way that does not compromise other Sustainable Development Goals.